EDUKASI HIPERTENSI KEHAMILAN FAKTOR PREDISPOSISI KEJADIAN STUNTING - Nurmayani, Winda; Wasliah, Indah; Rispawati, Bq. Heni; Halid, Sopian; Aswati, Aswati (Stikes Yarsi Mataram, 2024)
Hypertension in pregnancy is one of the most important problems faced by public health because HDK is a major cause of maternal and fetal morbidity and mortality. In pregnancy with preeclampsia, trophoblast cell invasion only occurs in part of the spiral arteries in the myometrial area so that placental function is disrupted, then the placenta does not meet the needs of blood for nutrients and oxygen to the fetus so that impaired placental function can cause stunted fetal growth which causes stunting. The purpose of this service is to educate the public about the dangers of pregnancy hypertension, because it is a predisposing factor to stunting. Method: Education is done by gathering the community in one place. The material is delivered by interactive lecture method using LCD and LCD projector. Result: the community is very enthusiastic about the material presented. Conclusion: this educational activity is also Conclusion: This educational activity has a positive impact on mothers and families, because the educational activities can increase knowledge for mothers and their children about the prevention of hypertension in pregnancy and the incidence of stunting.